Business Review : Revision and Extension For Intermediate Level Students - Bruce, Kay ; Parrish, Betsy and Wood, Allan (Harlow Longman House, 1993)
"Business Review" is for business people who want to refresh their Englsih and put it into action in a business context. It revises key grammar and functions while building up effective communication skills. Particular focus is given to listening and speaking skills in business situations.
Include Picture
Keywords: English language -- English language--Business English